RELATIONSHIP BETWEEN METEOROLOGICAL CONDITION PARAMETERS AND SEISMOTECTONICAL PROCESSES IN SEISMOGENERATING REGIONS - Ігнатишин, Василь; Малицький, Дмитро; Іжак, Тібор; Молнар, Д; Рац, Адальберт; Ігнатишин, Адальберт; Ігнатишин, Моніка (SWorldJournal, 2025)
The paper considers the meteorological state of the Transcarpathian internal trough, its geodynamic and seismic aspects. The study of variations in the meteorological field parameters, the reaction to them of modern horizontal movements in the Oash deep